2015
DOI: 10.1128/jvi.01137-15
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Analysis of Rare Norovirus Recombinants from Coinfected Mice Using Drop-Based Microfluidics

Abstract: Human noroviruses (HuNoVs) are positive-sense RNA viruses that can cause severe, highly infectious gastroenteritis. HuNoV outbreaks are frequently associated with recombination between circulating strains. Strain genotyping and phylogenetic analyses show that noroviruses often recombine in a highly conserved region near the junction of the viral polyprotein (open reading frame 1 [ORF1]) and capsid (ORF2) genes and occasionally within the RNA-dependent RNA polymerase (RdRP) gene. Although genotyping methods are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 59 publications
(72 reference statements)
0
33
0
Order By: Relevance
“…Table 1. Continued Continued recombination breakpoints have been identified across the norovirus genome, they are most frequently found in the ORF1-ORF2 junction region [29][30][31][32][33][34][35][36]. Dual typing (ORF1-RdRp=P type, ORF2=genotype) is now used routinely in many laboratories worldwide and at least 14 GI P-types and 27 GII P-types as well as 9 GI capsid genotypes and 22 GII capsid genotypes have been described [2,19,27].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1. Continued Continued recombination breakpoints have been identified across the norovirus genome, they are most frequently found in the ORF1-ORF2 junction region [29][30][31][32][33][34][35][36]. Dual typing (ORF1-RdRp=P type, ORF2=genotype) is now used routinely in many laboratories worldwide and at least 14 GI P-types and 27 GII P-types as well as 9 GI capsid genotypes and 22 GII capsid genotypes have been described [2,19,27].…”
Section: Introductionmentioning
confidence: 99%
“…From the data presented here, the GI and GII polyproteins appeared to be cleaved similarly, with both proteases showing similar activity on the heterologous substrates, suggesting that recombination within the polyprotein would not necessarily be restricted by differences in polyprotein cleavage. Recent work by Zhang et al ( 44 ) on two MNV strains has demonstrated the generation in vivo of a variety of recombinants throughout the polyprotein region. Notably, the two strains used (CW3 and WU20) possessed highly similar cleavage sites.…”
Section: Discussionmentioning
confidence: 99%
“…We modified the above assay to determine the concentration of recombinants resulting from a macrophage cell‐culture co‐infected with a mixture of both parental viruses, each with a multiplicity of infection of 2. We use a one‐step differential RT‐PCR cocktail where each of the two primers is specific to only one parental virus, in order to selectively amplify those recombinants where template switching occurs in a selected 1205 bp region (Figure A; the top row of the gels confirms that our cocktail amplified recombinants from the co‐infection without amplifying parental viruses in the viral mixture). For our drop‐based assay, the differential RT‐PCR cocktail was co‐encapsulated with viral templates, and in‐drop RT‐PCR was performed off‐chip.…”
Section: Figurementioning
confidence: 99%
“…Interestingly, Drop‐9 also includes a synonymous transversion at nucleotide 5221. Using this method, the first recombinant (from Drop‐1 sequence) was also detected from in vivo samples by examining the feces of mice that were co‐infected with both parental strains …”
Section: Figurementioning
confidence: 99%